Pain in Multiple Sclerosis: Understanding Pathophysiology, Diagnosis, and Management Through Clinical Vignettes - Racke, Michael K.; Frohman, Elliot M.; Frohman, Teresa (Frontiers in Neurology, 2022)
Neuropathic pain and other pain syndromes occur in the vast majority of patients with multiple sclerosis at some time during their disease course. Pain can become chronic and it can be paroxysmal. In this review, we will utilize clinical vignettes to describe various pain syndromes associated with multiple sclerosis and describe their pathophysiology. These syndromes vary from central neuropathic pain or Lhermitte’s phenomenon associated with central nervous system lesions to trigeminal neuralgia and optic neuritis pain associated with nerve lesions. Muscular pain can also arise due to spasticity. In addition, we will discuss strategies utilized to help patients manage these symptoms.